Outside is the ocean - Lansburgh, Matthew (Iowa short fiction award., 2017)
"Three days after her twentieth birthday, a young woman who grew up in Germany during World War II, crosses the Atlantic to start a new life. Outside Is the Ocean traces Heike's struggle to find love and happiness in America. After two marriages and a troubled relationship with her son, Heike adopts a disabled child from Russia, a strong-willed girl named Galina, who Heike hopes will give her the affection and companionship she craves. As Galina grows up, Heike's grasp on reality frays, and she writes a series of letters to the son she thinks has abandoned her forever. It isn't until Heike's death that her son finds these letters and realizes how skewed his mother's perceptions actually were"--